Epidermoid Cyst of the Testis: Unveiling a Rare and Uncommon Diagnosis - Vladimer Papava; Giorgi Sinauridze; Valeriane Kvakhajelidze; Andro Dzneladze; Irakli Gakhokidze; Leli Shanidze; Levani Donadze; Tamar Didbaridze; Tamta Mamasakhlisi; Ema Gergedava; et al. (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
Epidermoid cysts of the testis are rare benign tumors that often pose a diagnostic challenge due to their clinical and radiological resemblance to malignant testicular masses. Accurate differentiation is crucial to avoid unnecessary radical surgical interventions. The case of a 27-year-old male who presented with dull pain and progressive enlargement of the left testicle over several months has been reported. Physical examination revealed an enlarged, dense, and irregular left testicle, with no history of trauma or inflammation. Scrotal ultrasonography identified a heterogeneous mass measuring 25 x 17 x 18 mm with minimal vascularization. Laboratory tests, including AFP, B-HCG, and LDH, were within normal limits. Imaging with a chest, abdominal, and pelvic CT scan showed no signs of metastatic disease. The patient underwent a left-sided radical orchiectomy, during which a 7-8 mm lymph node was excised from the inguinal canal. Histopathological examination confirmed the diagnosis of an epidermoid cyst, characterized by a cystic structure lined with stratified squamous epithelium filled with keratinous material. This case highlights the importance of early and accurate diagnosis in distinguishing epidermoid cysts from malignant testicular tumors, enabling organ-sparing surgery when appropriate. The report underscores the need for further studies to enhance the characterization and differentiation of these rare entities.